Tìm x:
2.(x-2)2=50
tìm x : típ
2 005 . ( x - 2 006 ) = 2005
[ ( x + 50 ) . 50 - 50 ] : 50 = 50
tìm x
a) 50%+2/3X=X+4
b) (2/4/5X+50)1/1/2=-50
tìm x:
x + 50 - 40 = 50 + 50 x 2
x + 50 - 40 = 50 + 100
x + 50 - 40 = 150
x + 50 = 150 + 40 = 190
x = 190 - 50 = 140
x + 50 - 40 = 50 + 50 x 2
x + 50 - 40 = 150
x + 50 = 150 + 40
x + 50 = 190
x = 190 - 50
x = 140
ai k mik mik thề sẽ k lại hứa đó
x + 50 - 40 = 50 + 50 x 2
x + 50 - 40 = 50 x ( 1 + 2 )
x + 50 - 40 = 50 x 3
x + 50 - 40 = 150
x + 50 = 150 + 40
x + 50 = 190
x = 190 - 50
x = 140
mình nha
Tìm x (x mũ 2 + 1) + (x mũ 2 +2) + (x mũ 2 + 3) + (x mũ 2 +4) +… (x mũ 2 + 50) = 1475
(x² + 1) + (x² + 2) + ... + (x² + 50) = 1475
x² + 1 + x² + 2 + ... + x² + 50 = 1475
50x² + (1 + 2 + ... + 50) = 1475
50x² + 50 . 51 : 2 = 1475
50x² + 1275 = 1475
50x² = 1475 - 1275
50x² = 200
x² = 200 : 50
x² = 4
x = 2 hoặc x = -2
Tìm x biết
(x.2) + (x.2^2) + (x.2^3)+...+(x.2^50) = 2^51 + 498
tìm x:
x + 12 x 2 = 50 + 50
x + 12 x 2 = 50 + 50
x + 12 x 2 = 100
x + 24 = 100
x = 100 - 24
x = 76
x + 12 x 2 = 50 + 50
x+12x2=100
x+24=100
x=100-24
x=76
x + 12 x 2 = 50 + 50
x + 24 = 100
x = 100 - 24
x = 76
k mk nha
Tìm x:
2.(x-2)2=50
2.(x-2)^2=50
=>(x-2)^2=50:2=5^2
=>x-2=5
=>x=7
tìm x: 2x - 2 + 2 + 2 + 6 x 5x = 50
=>2x+2+6.5x=50
=>2x+2+30x=50
=>2x+30x=50-2
=>32x=48
=>x=48:32
=>x=3/2
tìm x:
x + 10 x 2 = 50 x 2
x + 10 x 2 = 50 x 2
x + 20 = 100
x = 100 - 20
x = 80
tìm x:
x + 10 x 2 = 50 x 2
=>x+10x2=100
=>x+20=100
=>x=100-20
=>x=80
bấm **** nha
x + 10 x 2 = 50 x 2
x + 10 x 2 = 100
x + 10 = 100 : 2
x + 10 = 50
x = 50 - 10
x = 40
ai nhanh mik k
tìm x (2/5-x)^3 .50% =1/2
`(2/5-x)^3*50%=1/2`
`=>(2/5-x)^3*1/2=1/2`
`=>(2/5-x)^3=1/2:1/2`
`=>(2/5-x)^3=1`
`=>2/5-x=1`
`=>x=2/5-1`
`=>x=2/5-5/5`
`=>x=-3/5`
\(\left(\dfrac{2}{5}-x\right)^3\times50\%=\dfrac{1}{2}\\ \Rightarrow\left(\dfrac{2}{5}-x\right)^3\times\dfrac{1}{2}=\dfrac{1}{2}\\ \Rightarrow\left(\dfrac{2}{5}-x\right)^3=\dfrac{1}{2}:\dfrac{1}{2}\\ \Rightarrow\left(\dfrac{2}{5}-x\right)^3=\dfrac{1}{2}\times2\\ \Rightarrow\left(\dfrac{2}{5}-x\right)^3=1\\ \Rightarrow\dfrac{2}{5}-x=1\\ \Rightarrow x=\dfrac{2}{5}-1\\ \Rightarrow x=\dfrac{2}{5}-\dfrac{5}{5}\\ \Rightarrow x=\dfrac{-3}{5}\)